Estimates for λ-spirallike function of complex order on the boundary - Akyel, T. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.5 We give some results for λ -spirallike function of complex order at the boundary of the unit disc U. The sharpness of these results is also proved. Furthermore, three examples for our results are considered.